ECONOMIC IMPACTS OF THE COVID-19 PANDEMIC ON THE HOTEL BUSINESS IN ZIMBABWE - Felicity N Ncube; Oliver Chikuta; Vitalis Basera; Rudorwashe Baipai; Precious Mazhande; Musawenkosi Tapfuma (Bahasa Indonesia, 2021)
It is evident from literature that the spread of the Covid-19 pandemic has brought the world economiesto its ‘knees’. No industry has gone untouched by the effects of this pandemic. Globally there has beenan adverse impact on travel which is backbone of the hotel industry. This study focuses on exploringthe impact that the Covid-19 pandemic has had on Zimbabwean hotel sector. The objectives of thestudy focused on investigating the impact of Covid-19 pandemic on hotel occupancy and revenue andproposing strategies that can be implemented for recovery post the pandemic. The study adopted amixed method approach, semi-structured questionnaires were used to gather data from 29 (3-5 star) hotel management across the various major tourism cities in Zimbabwe. Findings reveal that the Covid-19 pandemic has had an adverse impact on hotel occupancy and revenue. Occupancy and revenue have dropped. Strategies have been employed by hotel to cope with the adverse impact of reducedoccupancy and revenue, these include working with minimal staff to avoid increases exposure, closingother parts of the hotel to reduce operational cost and operating on take out bases. It can be concludedthat hotels in Zimbabwe are not prepared for pandemics like Covid-19. It is therefore recommendedthat disaster management plans relating to pandemics be developed and implemented by hotels.